2021
DOI: 10.1111/anu.13381
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid‐enriched diets improved the growth and flesh quality of grass carp ( Ctenopharyngodon idellus ) based on metabolomics

Abstract: Flavonoids are a large group of bioactive compounds from plants with 2-phenylchromone as the skeleton, including berries, apples, onions, cocoa and tea. The representative flavonoids mainly include baicalein (BC), rutin (RT), quercetin (QC), tangerine, glycyrrhizin and catechin (CC), which have biological properties like antioxidant, anti-inflammatory and antibacterial (Manach et al., 2004;Zhang et al., 2011). Due to the antioxidant properties, the chronic consumption of foods rich in flavonoids has been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The present study demonstrated that dietary PPP, even at low levels, significantly stimulated the growth performance, feed utilization efficiency and crude protein content of Nile tilapia. These results may be due to the phenolic compounds present in PPP, namely gallic and ferulic acids (Dhaoudia et al 2013 ; Benayad et al 2014 ), which are renowned as growth promoters (Cai et al 2020 ; Dawood et al 2020 ; Van Doan et al 2021c ; Xu et al 2021 ). The improvement of the feed utilization efficiency and body protein content in the present study may be attributed to the ability of dietary PPP to stimulate the digestive enzymes secretion and promote the intestinal microbiota function to digest the nutrients and improve their absorption (Salem et al 2019 ; Van Doan et al ( 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that dietary PPP, even at low levels, significantly stimulated the growth performance, feed utilization efficiency and crude protein content of Nile tilapia. These results may be due to the phenolic compounds present in PPP, namely gallic and ferulic acids (Dhaoudia et al 2013 ; Benayad et al 2014 ), which are renowned as growth promoters (Cai et al 2020 ; Dawood et al 2020 ; Van Doan et al 2021c ; Xu et al 2021 ). The improvement of the feed utilization efficiency and body protein content in the present study may be attributed to the ability of dietary PPP to stimulate the digestive enzymes secretion and promote the intestinal microbiota function to digest the nutrients and improve their absorption (Salem et al 2019 ; Van Doan et al ( 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was filtered, and 4 mL of distilled water was added to the centrifuge (Cence HT160, Changsha, China) for 5 min at 4 °C (2300 g), and then the supernatant was removed to concentrate the lower layer. Subsequently, 1 mL of chromatographically pure n-hexane was added to dissolve the lipid, and 1 mL of 0.4 mol/L potassium hydroxide–methanol solution was added for 30 min to carry out methyl esterification, followed by the addition of 2 mL of deionized water, and then the upper layer of the solution was extracted after being separated and detected and analyzed by gas chromatography, and the contents of the various fatty acids were calculated according to the area-normalized method [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, EGCG stimulates aerobic metabolism and inhibits anaerobic metabolism in muscles. Similarly, other plant extracts, such as quercetin [39], resveratrol [40], E. ulmoides extracts [41], and grape seed proanthocyanidin extract [42], reportedly decrease the glycolytic potential of muscles and enhance aerobic metabolism in fish, pigs, and broilers, resulting in reduced lactate levels.…”
Section: Egcg Supplementation Improved the Physical Andmentioning
confidence: 99%